1997
DOI: 10.1159/000108221
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Reversal of the Uncal Syndrome and Brain Edema from Infarction in the Middle Cerebral Artery Territory

Abstract: Brain edema following ischemic stroke often results in significant morbidity and death. Decompressive craniotomy has been advocated and may result in a surprisingly satisfactory outcome. We present a 17-year-old patient who developed a right middle cerebral artery territory infarction associated with a cardiac myxoma. Five days after the ictus and two days after a thoracotomy to remove the obstructing tumor, he developed clinical signs of uncal herniation. CT scans showed massive cerebral edema and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…Patients that underwent HC were significantly younger than the NHC group. Wijdicks and colleagues 26 suggested that ICP in younger patients might rise rather quickly due to less reserve to compensate for the increase in volume. Certain degrees of age-related cerebral atrophy might protect older patients from space-occupying brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Patients that underwent HC were significantly younger than the NHC group. Wijdicks and colleagues 26 suggested that ICP in younger patients might rise rather quickly due to less reserve to compensate for the increase in volume. Certain degrees of age-related cerebral atrophy might protect older patients from space-occupying brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…However, Frank 30 has demonstrated that elevated ICP is not a common cause of initial neurological deterioration from large hemispheric stroke. Because in most patients cerebral edema contributes to the gradual build-up of a mass, displacing the brain stem rather than globally increasing ICP, Wijdicks and colleagues 34 suggest that ICP in younger patients might rise rather quickly due to less reserve to compensate for the increase in volume. Our own data 35 from patients in whom ICP was monitored during severe MCA infarction showed a correlation of high ICP and poor clinical outcome.…”
Section: Comparison Of Parameters Among Late and Early Hemicraniectommentioning
confidence: 99%
“…In patients with malignant CVA, a large area of parenchymal hypodensity in the MCA territory is often visualized on the admission CT scans (Figure 1). (59,64,74,78) With progressive clinical deterioration, CT-demonstrated signs may also include mass effect, effacement of the basal cisterns, compression of the ventricular system, a shift of midline structures, (78,74) and herniation of tissue through the falx, foramen magnum, or tentorium. These patients present clinically with progressive deterioration of consciousness within the first 2 days.…”
Section: Historical Backgroundmentioning
confidence: 99%